Multifactor Regulation of the MdtJI Polyamine Transporter in Shigella. - Adriano Leuzzi; Maria Letizia Di Martino; Rosaria Campilongo; Maurizio Falconi; Marialuisa Barbagallo; Lucia Marcocci; Paola Pietrangeli; Mariassunta Casalino; Milena Grossi; Gioacchino Micheli; Bianca Colonna; Gianni Prosseda (PLoS ONE, 2015)
The polyamine profile of Shigella, the etiological agent of bacillary dysentery in humans, differs markedly from that of E. coli, its innocuous commensal ancestor. Pathoadaptive mutations such as the loss of cadaverine and the increase of spermidine favour the full expression of the virulent phenotype of Shigella. Spermidine levels affect the expression of the MdtJI complex, a recently identified efflux pump belonging to the small multi-drug resistance family of transporters. In the present study, we have addressed the regulation of the mdtJI operon in Shigella by asking which factors influence its expression as compared to E. coli. In particular, after identifying the mdtJI promoter by primer extension analysis, in vivo transcription assays and gel-retardation experiments were carried out to get insight on the silencing of mdtJI in E. coli. The results indicate that H-NS, a major nucleoid protein, plays a key role in repressing the mdtJI operon by direct binding to the regulatory region. In the Shigella background mdtJI expression is increased by the high levels of spermidine typically found in this microorganism and by VirF, the plasmid-encoded regulator of the Shigella virulence regulatory cascade. We also show that the expression of mdtJI is stimulated by bile components. Functional analyses reveal that MdtJI is able to promote the excretion of putrescine, the spermidine precursor. This leads us to consider the MdtJI complex as a possible safety valve allowing Shigella to maintain spermidine to a level optimally suited to survival within infected macrophages and, at the same time, prevent toxicity due to spermidine over-accumulation.